![\qquad\qquad\huge\underline{{\sf Answer}}](https://img.qammunity.org/2023/formulas/mathematics/college/c2sxngg8eo14b80i5ilhws8elkvsue4xqb.png)
The given sequence is in Arithmetic progression, and we have to find its nth term ~
So, let's get it solved ~
First term of the sequence is :
Common difference is :
Now, if we have to write the 2nd Term with respect to first one, we can write :
- 2nd Term = a + (2 - 1)d = a + d = 2 + 2 = 4
similarly ~
- 3rd Term = a + (3 - 1)d = a + 2d = 2 + 4 = 6
- 4th Term = a + (4 - 1)d = a + 3d = 2 + 6 = 8
Therefore, I similar pattern ~
![\qquad \sf \dashrightarrow \: nth \: term = a + (n - 1)d](https://img.qammunity.org/2023/formulas/mathematics/high-school/liu2cd3ntlrtl0ywrp12u7907bmohltmjp.png)
![\qquad \sf \dashrightarrow \: nth \: term = 2 + (n - 1)2](https://img.qammunity.org/2023/formulas/mathematics/high-school/wjvywt4ve17lg4vxbn5ybbupoly5n23lzn.png)
![\qquad \sf \dashrightarrow \: nth \: term = 2(1 + (n - 1))](https://img.qammunity.org/2023/formulas/mathematics/high-school/ek0bzybdrgabpf6xtyhxe3ql841xnavdhq.png)
![\qquad \sf \dashrightarrow \: nth \: term = 2(1 + n - 1)](https://img.qammunity.org/2023/formulas/mathematics/high-school/173jj3f8hfuxngips40ju85lvvgolg4iwx.png)
![\qquad \sf \dashrightarrow \: nth \: term = 2 n](https://img.qammunity.org/2023/formulas/mathematics/high-school/7prfb8d8m24m9c6a7nt5iujcii8ctjhhgu.png)
Feel free to ask your doubts, if you have any ~